Research Areas in Distance Education: A Delphi Study - Zawacki-Richter, Olaf (International Review of Research in Open and Distributed Learning, 2009)
This study had three purposes: Firstly, to develop a categorization of research areas in distance education; secondly, to identify the most important research areas in distance education; and thirdly, to identify the most neglected research areas in distance education. Based on a literature review and a Delphi study, three broad levels or perspectives with 15 research areas were derived to organize the body of knowledge in distance education. Prospective researchers can use the results to identify gaps and priority areas and to explore potential research directions.